2021
DOI: 10.1007/s00125-020-05352-9
|View full text |Cite
|
Sign up to set email alerts
|

Axonal swellings are related to type 2 diabetes, but not to distal diabetic sensorimotor polyneuropathy

Abstract: Aims/hypothesis Distal diabetic sensorimotor polyneuropathy (DSP) is a common complication of diabetes with many patients showing a reduction of intraepidermal nerve fibre density (IENFD) from skin biopsy, a validated and sensitive diagnostic tool for the assessment of DSP. Axonal swelling ratio is a morphological quantification altered in DSP. It is, however, unclear if axonal swellings are related to diabetes or DSP. The aim of this study was to investigate how axonal swellings in cutaneous ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In some of these patients, microneurography or genetics is needed to make the final diagnosis [42]. Another approach has been to increase the sensitivity by using more parameters in skin biopsy than merely the intraepidermal nerve fibre density, for example, assessing dermal nerve fibres [43] or nerve fibre swellings [44], or the quantification of nerve fibre subtypes [45,46]. Recent skin biopsy studies investigating possible pathological biomarkers of pain found that peptidergic and regenerating fibre immunostaining in patients with diabetic neuropathy is closely associated with neuropathic pain [45,47].…”
Section: S Kin B Iopsymentioning
confidence: 99%
“…In some of these patients, microneurography or genetics is needed to make the final diagnosis [42]. Another approach has been to increase the sensitivity by using more parameters in skin biopsy than merely the intraepidermal nerve fibre density, for example, assessing dermal nerve fibres [43] or nerve fibre swellings [44], or the quantification of nerve fibre subtypes [45,46]. Recent skin biopsy studies investigating possible pathological biomarkers of pain found that peptidergic and regenerating fibre immunostaining in patients with diabetic neuropathy is closely associated with neuropathic pain [45,47].…”
Section: S Kin B Iopsymentioning
confidence: 99%
“…The Toronto Consensus (2011) [ 2 ] defined DDSP pain as “ pain that is a direct consequence of abnormalities in the peripheral somatosensory nervous system in diabetic individuals ”. Diagnostic of DSSN is frequently delayed due to the scarcity of early diagnostic tests, and recently, axonal swellings in cutaneous biopsies have been proposed as an early marker of sensory nerve injury in type 2 diabetes mellitus [ 4 , 5 ]. Consequently, there is a high risk of ulceration with subsequent distal amputation in lower limbs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…), blinded to the origin and clinical features of the subjects, performed the entire process based on published data. 25 Axonal swellings were defined as the enlargements greater than 1.5 μm, as per previous publications e.g., [26][27][28] Swellings smaller than 1.5 μm were considered normal. The dimensions of axonal swellings were measured using stereological software NewCast (Horesholm, Denmark).…”
Section: Skin Biopsymentioning
confidence: 99%